2017
DOI: 10.1175/jcli-d-16-0435.1
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Synoptic Disturbance in the Extreme Rainfall at Cherrapunji, Northeast India, Based on 104 Years of Rainfall Data (1902–2005)

Abstract: The characteristics of active rainfall spells (ARSs) at Cherrapunji, northeast India, where extreme high rainfall is experienced, and their relationships with large-scale dynamics were studied using daily rainfall data from 1902 to 2005 and Japanese 55-Year Reanalysis from 1958 to 2005. Extreme high daily rainfalls occur in association with ARSs. The extremely large amounts of rainfall in the monsoon season are determined by the cumulative rainfall during ARSs. ARSs start when anomalous anticyclonic circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Negative rainfall anomalies over the central part of India ( Fig. 1c, d) are shown to have apparent associations with Rossby wave response induced by convectively stable anomalies seen over the Bay of Bengal (Krishnan et al 2000), and also in part with westward propagating lowlevel circulation anomalies from the western North Pacific (Murata et al 2017). The circulation anomalies seen over East Asia (Fig.…”
Section: Circulation and Rainfall Diagnosis Duringmentioning
confidence: 84%
See 1 more Smart Citation
“…Negative rainfall anomalies over the central part of India ( Fig. 1c, d) are shown to have apparent associations with Rossby wave response induced by convectively stable anomalies seen over the Bay of Bengal (Krishnan et al 2000), and also in part with westward propagating lowlevel circulation anomalies from the western North Pacific (Murata et al 2017). The circulation anomalies seen over East Asia (Fig.…”
Section: Circulation and Rainfall Diagnosis Duringmentioning
confidence: 84%
“…While a decrease in upper tropospheric divergence during ISM breaks due to suppressed monsoon convection over the Indian subcontinent can induce a downstream Rossby wave response towards East Asia (Krishnan et al 2009), it is not yet clear if the monsoonal heating anomalies can have any further consequences on large-scale circulation patterns. Murata et al (2017) noted that extreme rain periods over Cherrapunji, the wettest place on Earth located over the CEH, had associations with westward propagating low-level circulation anomalies from the western North Pacific. Their results further indicated that a large number of extreme rain periods over Cherrapunji were coincident with ISM breaks.…”
Section: Introductionmentioning
confidence: 99%
“…The subtropical westerly jet stream and tropical easterly jet stream together show a southward shift during extreme rainfall days and the axis of this couplet recedes north to the earlier position after the extreme activity; this result is consistent with the findings of Murata et al . (). The core of the negative relative vorticity during high rainfall activity lies around 25 ° N, and before and after the event the core is shifted farther north to north of 30 ° N. In general, the spatial structure of the wind pattern and vorticity explain the favourable conditions for enhanced rainfall activity over the northeast regions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, intraseasonal variation (about 2~4 weeks) was found, with depletion occurring in mid-May, mid-June, early and late August, and early October. Fujinami et al (2011) and Murata et al (2017) showed that the intraseasonal variation of precipitation was dominant around Cherapunji in the northeastern part of India. These results indicate that the δ 18 O value of precipitation over Bangladesh can be controlled by seasonal and intraseasonal variations (e.g., the ISM and monsoon low-pressure system).…”
Section: Seasonal Variation In the Amount And Isotopic Composition Ofmentioning
confidence: 99%